Analysis of back-face strain measurement for adhesively bonded single lap joints using strain gauge, Digital Image Correlation and finite element method. (March 2020) - Weiland, J.; Sadeghi, M.Z.; Thomalla, J.V.; Schiebahn, A.; Schroeder, K.U.; Reisgen, U.
Abstract: Back-face strain measurement is a widely used method for damage detection of adhesively bonded single lap joints. Often, a simple Strain Gauge is used to monitor in-situ structural adhesives bonds in the field. However, the extrinsic local placement of the Strain Gauge on the strain hot spot of the joint poses a major challenge. Furthermore, finite element method (FEM) simulations do not reproduce the adherents accurately enough due to inaccuracies in the manufacturing process. Therefore, an additional optical measurement methodology is required to precisely analyze and localize the strain hot spots on the adherent. This work deals with the most important theoretical background on the stiffness, strength and fracture behaviour of the single lap joint. Subsequently, the back-face strain along the joint part was simulated by means of FEM. The results were validated and implemented with the results of the Digital Image Correlation (DIC). The strains in the hot spot area were determined from both finite element (FE) and DIC methods. With this knowledge, the Strain Gauge is applied exactly to the location of the strain hot spot. The central result of the paper is the confirmation of the strain hot spot. It is shown that the calculated points and curves can be approximated very well.